2
$\begingroup$

I guess for the modified Bessel funcion $K_0(z)$, $$\sum_{n=1}^\infty K_0(s\, n) \sim \frac{-2\log 2 - \log \pi + \gamma}{2} + \frac{\log s}{2} + \frac{\pi}{2\, s}, \quad s\to 0^+,$$ if taking $$\sum_{n=1}^\infty 1 =\zeta(0),$$ and $$\sum_{n=1}^\infty \log n = \log \prod_{n=1}^\infty n=\log \sqrt{2\pi},$$ I can get all the rest terms, but where does the term $\frac{\pi}{2\,s}$ come from?

$\endgroup$
3
$\begingroup$

The term $\frac{\pi}{2s}$ comes from the pole of $\zeta(s)$. Let's use the fact that Mellin transform of $K_0(s)$ equals $$ \int_0^{+\infty} K_0(s)s^{t-1}ds=2^{t-2}\Gamma^2(t/2). $$

From this we get that if $f(s)=\sum_{n} K_0(sn)$ then for $\mathrm{Re}\,s>1$ we have

$$ \int_0^{+\infty} f(s)s^{t-1}ds=2^{t-2}\Gamma^2(t/2)\zeta(t) $$

Therefore, by Mellin inversion we get

$$ f(s)=\frac{1}{2\pi i}\int_{3/2-i\infty}^{3/2+i\infty} 2^{t-2}\Gamma^2(t/2)\zeta(t)s^{-t}dt. $$

Now, if you move your contour far to the left, you will encounter poles of the integrand at the points $t=1,0,-2,-4,-6\ldots$. Using the fact that $\Gamma$ decays exponentially on the vertical lines and $\zeta$ grows at most polynomially, we obtain for any $N$

$$ f(s)=\mathrm{Res}_{t=1} 2^{t-2}\zeta(t)\Gamma^2(t/2)s^{-t}+\sum_{n=0}^{N} \mathrm{Res}_{t=-2n} 2^{t-2}\zeta(t)\Gamma^2(t/2)s^{-t}+O(s^{-1-2N}) $$

Computation of the first term reveals the desired $\frac{\pi}{2s}$ term, as $\Gamma(1/2)^2=\pi$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.